Mongolian Prime Minister Visits (Institutional Knowledge at Singapore Management University, 2002)
Singapore Management University hosts an entourage of education, business and manufacturing leaders from Mongolia. In centre, from left to right: Mongolian Prime Minster Nambaryn Enkhbayar, Singapore Minister for State for Health, Environment and Transport Balaji Sadasivan, and SMU President Ronald Frank. Photo taken on 11 October 2002.